Respon India Terhadap Belt Road Initiatives oleh Presiden Xi Jinping Melalui Asia Africa Growth Corridor - Salsabillah, Callula; Aryani, Maria Indira (Global and Policy Journal of International Relations, 2021)
AbstractThe Belt and Road Initiative, which was initiated by China in 2013, is a multilateral foreign policy strategy that is not only in the form of cooperation in an economic scheme, but BRI also provides loans in the form of infrastructure investment to countries that join this project. India, as a country that considers BRI a threat to its country, has made an act to drive an economic scheme called the Asia Africa Growth Corridor with Japan and other countries in Africa. This action was carried out by India by cooperating with countries that have similar views on BRI and countries that have both suffered losses from the establishment of BRI by President Xi Jinping. This phenomenon is a form of balancing, in the theory of Balance of Power by Kenneth Waltz. This article aims to determine the balancing perspective in seeing the formation of AAGC by India as a counter form to China's BRI project. Keywords: India, Balancing, Balance of Power, Asia Africa Growth Corridor, Belt and Road Initiatives.AbstrakBelt and Road Initiative yang diinisiasi oleh Tiongkok pada 2013 lalu adalah strategi politik luar negeri yang bersifat multilateral yang tidak hanya berupa kerjasama dalam skema ekonomi, tetapi BRI juga menyediakan pinjaman dalam bentuk investasi infrastruktur pada negara yang bergabung dalam proyek ini. India sebagai salah satu negara yang menganggap BRI adalah suatu ancaman bagi negaranya, membuat India bertindak untuk menggerakkan sebuah skema ekonomi bernama Asia Africa Growth Corridor bersama Jepang dan negara-negara di Afrika. Tindakan ini dilakukan India dengan menggandeng negara yang memiliki pandangan serupa terhadap BRI dan negara yang sama-sama ditimpa kerugian atas dibentuknya BRI oleh presiden Xi Jinping. Fenomena ini merupakan suatu bentuk Balancing, dalam teori Balance of Power oleh Kenneth Waltz. Penelitian ini bertujuan untuk mengetahui perspektif balancing dalam memandang dibentuknya AAGC oleh India sebagai bentuk counter terhadap proyek BRI milik Tiongkok. Kata Kunci: India, Balancing, Balance of Power, Asia Africa Growth Corridor, Belt and Road Initiatives.  DOI : https://doi.org/10.33005/jgp.v9i2.3012